Functional characterisation of wheat Pgip genes reveals their involvement in the local response to wounding. (10th April 2013) - Janni, M.; Bozzini, T.; Moscetti, I.; Volpi, C.; D'Ovidio, R.
Abstract: Polygalacturonase‐inhibiting proteins (PGIPs) are cell wall leucine‐rich repeat (LRR) proteins involved in plant defence. The hexaploid wheat ( Triticum aestivum, genome AABBDD) genome contains one Pgip gene per genome. Tapgip1 (B genome) and Tapgip2 (D genome) are expressed in all tissues, whereas Tapgip3 (A genome) is inactive because of a long terminal repeat, Copia retrotransposon insertion within the coding region. To verify whether Tapgip1 and Tapgip2 encode active PGIPs and are involved in the wheat defence response, we expressed them transiently and analysed their expression under stress conditions. Neither TaPGIP1 nor TaPGIP2 showed inhibition activity in vitro against fungal polygalacturonases. Moreover, a wheat genotype ( T. turgidum ssp. dicoccoides ) lacking active homologues of Tapgip1 or Tapgip2 possesses PGIP activity. At transcript level, Tapgip1 and Tapgip2 were both up‐regulated after fungal infection and strongly induced following wounding. This latter result has been confirmed in transgenic wheat plants expressing the β‐glucuronidase (GUS) gene under control of the 5′‐flanking region of Tdpgip1, a homologue of Tapgip1 with an identical sequence. Strong and transient GUS staining was mainly restricted to the damaged tissues and was not observed in adjacent tissues. Taken together, these results suggest that Tapgip s and their homologues are involved in the wheat defence response by acting at the site of the lesion caused by pathogen infection.